Ustekinumab: “Real-world” outcomes and potential predictors of nonresponse in treatment-refractory Crohn’s disease - Hoffmann, Peter (World J Gastroenterol, 2019)
BACKGROUND: Ustekinumab was approved in Europe for the treatment of adults with moderate to severe Crohn's disease (CD) in 2016, and there is an urgent need for data on its everyday use. AIM: To obtain data on the daily use of ustekinumab. METHODS: This is a retrospective monocentric study. Patients with moderate to severe CD who began ustekinumab therapy at the inflammatory bowel diseases outpatient clinic of the Heidelberg University Hospital between December 2016 and March 2018 were selected based on electronic patient files. The primary study endpoint was combined steroid-free clinical remission or steroid-free clinical response at 24 ± 6 wk of ustekinumab therapy. Secondary study endpoints were: achievement of mucosal healing, sonographic and magnetic resonance imaging response, biochemical response, the need for intestinal surgery within 24 ± 6 wk after treatment initiation, the occurrence of adverse events, treatment discontinuation due to nonresponse or adverse events, improvement of extraintestinal manifestations, clinical response at 48 ± 6 wk of therapy, and association of response with nucleotid oligodimerisation domain 2 mutations. RESULTS: Fifty-seven patients with CD (5.3% anti-tumour necrosis factor α naïve, 63.2% having undergone at least one intestinal surgery) were included in the study. Twenty patients (35.1%) achieved steroid-free clinical remission, 6 (10.5%) steroid-free clinical response and 31 (54.4%) were non-responders. Treatment discontinuation due to adverse events occurred in two patients (3.5%). Male sex, the presence of extraintestinal manifestations and the use of steroids at baseline were predictors of nonresponse to ustekinumab therapy. CONCLUSION: In a “real-world” treatment-refractory cohort of patients with CD, ustekinumab appeared efficacious and safe.